Effect of bed size on hydrodynamics in 3‐D gas–solid fluidized beds. Issue 5 (6th February 2015) - Verma, Vikrant; Padding, Johan T.; Deen, Niels G.; (Hans) Kuipers, J. A. M.
<x xml:space="preserve">Abstract</x> It is well known that hydrodynamics observed in large scale gas–solid fluidized beds are different from those observed in smaller scale beds. In this article, an efficient two‐fluid model based on kinetic theory of granular flow is applied, with the goal to highlight and investigate hydrodynamics differences between three‐dimensional fluidized beds of diameter 0.10, 0.15, 0.30, 0.60, and 1.0 m, focusing on the bubble and solids flow characteristics in the bubbling regime. Results for the 0.30 m diameter bed are compared with experimental results from the literature. The bubble size evolution closely follows a correlation proposed by Werther for small beds, and a correlation proposed by Darton for sufficiently large beds. The bubble size increases as the bed diameter is increased from 0.10 to 0.30 m, and remains approximately constant for bed diameters from 0.30 to 1.0 m. Concurrently, an increase in bubble rise velocity is observed, with a much high bubble rise velocity in the largest bed of diameter 1.0 m due to gulf stream circulations. The dynamics in shallow and deep beds is predicted to be different, with marked differences in bubble size and solids circulation patterns. © 2015 American Institute of Chemical Engineers AIChE J, 61: 1492–1506, 2015